Early Eocene omomyid from the Nanjemoy Formation of Virginia: first fossil primate from the Atlantic Coastal Plain. Issue 1 (2nd January 2021) - Rose, Kenneth D.; Perry, Jonathan M. G.; Prufrock, Kristen A.; Weems, Robert E.
ABSTRACT: The first known primate fossil from the Atlantic Coastal Plain, a mandibular fragment representing the family Omomyidae, is described from the early Eocene Fisher/Sullivan Site in northeastern Virginia. The jaw, containing m1–m2, was found near the base of the Potapaco Member, Bed B, of the Nanjemoy Formation, indicating an early Ypresian age, ca. 54.5 Ma. As the specimen lacks diagnostic antemolar dentition, its precise identity cannot be confidently determined. However, its diminutive size and plesiomorphic molar morphology suggest that it represents a primitive omomyid. Comparison with a diversity of omomyids finds that nearly all omomyid genera are larger and/or derived in various features compared to the Nanjemoy specimen. Closest resemblances are to the primitive omomyids Steinius, Anemorhysis, Loveina, Melaneremia, and especially Teilhardina .